Replacement of the Native Mitral Valve Due to Endocarditis Caused by Stenotrophomonas Maltophilia - Ilker Alat; Ahmet Turhan Kılıç; Ersin Çelik (Brazilian Journal of Cardiovascular Surgery, 2019)
Abstract We report a case of a 59-year-old female patient with vegetative native mitral valve endocarditis caused by Stenotrophomonas maltophilia (SM). She had hemodialysis-dependent chronic renal failure, but no immunosuppressive disease. Echocardiography showed mobile vegetation on her native mitral valve. Right femoral artery embolectomy and mitral valve replacement were performed simultaneously. She awakened from anesthesia, but she passed away due to septic shock complications. To the best of our knowledge, this was the first case in whom native mitral valve endocarditis caused by SM was observed (despite of absence of any immunosuppressive event) and needed to undergo valve replacement.